Pembelajaran Fisika Berbasis Kompetensi Life Skill Kelas XII IPA.1 MAN 1 Lampung Selatan - Poniman, Poniman (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2016)
This study aims to determine the physics competency-based learning life skills class XII IPA1, It conducted in two cycles, each cycle consisting of four phases: planning, execution, analysis and reflection. The action used is